PENGUJIAN AKTIVITAS ANTIOKSIDAN EKSTRAK BUNGA LOTUS (Nelumbo nucifera) - Romadanu Romadanu; Siti Hanggita; Shanti Dwita Lestari (Jurnal FishtecH, 2014)
The purpose of this research was to observe antioxidant activity of lotus leaves extract (Nelumbo nucifera). The extractionÂ  process was carried out using three different solvents namely methanol, ethyl acetate and n-hexane. The observed parameters were extraction yields phytochemical compounds (alkaloid, flavonoid and tanin) and antioxidant activity using DPPH method. The results showed that the methanol extract exhibited the highest yield with a value of 0.708% and had a flavonoid tannin content of 1161 ppm. The antoxidant activity of the same extract as indicated by IC50 value was 199 ppm. The extract ethyl acetate and n-hexane solvents did not show potential antioxidant activities